KOMUNIKASI FANS JKT48 MELALUI PRIVATE MESSAGE (STUDI FENOMENOLOGI MENGENAI PENGALAMAN KOMUNIKASI FANS KEPADA IDOL JKT48) - Sekar Putri Khalisha (2023)
The pandemic, which created distance between members and fans, led JKT48 to create Private Messages as a one-way communication form using a broadcast message system on the LINE application. The purpose of this research is to understand the meaning, experiences, and communication patterns of fans towards JKT48 idols through JKT48 Private Messages, using a qualitative research method with a phenomenological approach to delve deeper into individuals' experiences with a particular phenomenon. The researcher collected data by conducting in-depth interviews with six JKT48 fans. Data analysis techniques included data grouping based on sub-themes, data elimination, thematization, data identification, data re-discussion, textual data merging, and meaning reconstruction. The results of this research indicate that fans interpret the communication that takes place through JKT48 Private Messages as that of an idol, a younger sister, and a friend. This interpretation is influenced by several factors, namely: 1) Age differences, 2) Shared hobbies, 3) Active participation of the idol in sending and listening to stories, and 4) The presence of communication distance towards privacy. Communication in JKT48 Private Messages forms a wheel-like communication pattern.